Digital Literacy for Millennial Families in Educating Children in the Digital Age - Muhammad Farhan; Triono Ali Musthofa (Didaktika: Jurnal Kependidikan, 2024)
The development of technological advancements in the digital age has brought about enormous changes in all aspects of life. In the digital age, educational problems have become very diverse with the increase in family responsibilities. To overcome these developments, the expertise of parents and educators is needed to implement appropriate solutions to all these problems as well as the ability to adapt to changing environments. This research takes an in-depth look at the digital literacy of millennial families in raising children in the digital age. Teachers and parents really need digital literacy skills to educate children so that they can play various roles as educators in the digital age. This research uses library research methods. Data collection in this research was carried out by developing various types of literature in the form of books, journals, e-books and literature relevant to digital literacy issues in millennial families in the digital age. Data analysis techniques use content analysis methods from journals and other materials accessible via the Internet. The results show that in the digital age, the role of parents is really necessary to avoid being left behind. In our time, a new reorientation of learning is necessary because it is seen to affect vision, responsibility, social sensitivity and logical abilities, as well as honesty. All this leads to a reorientation of the new role of parents, namely as agents of change, knowledge updaters and learning consultants who emphasize creativity, initiative, good communication and cooperation between parents, school and community